Summer. - Wharton, Edith (Floating Press, 1917)
A young girl from a rural New England town longs to escape her small community, but is unable to move beyond social restrictions and her own weaknesses of character. She meets a man by chance, who encourages the awakening of her sexuality. The ramifications of their relationship begin to unfold against a background of class and moral standards.